Comparative Study of Placental Cotyledons of Gir Cows and Jaffrabadi Buffaloes - Padodara, Ramesh J.; Singh, Vivek K.; Fefar, Dhaval T.; Savsani, Harish H.; Mehta, Vijay M. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was conducted to compare placental cotyledons’ structural and endocrine function between Gir cows and Jaffrabadi buffalo cows. Placentas were collected from 10 Gir cattle(Bos indicus) and 10 Jaffrabadi buffaloes (Bubalus bubalis) at the time of parturition to study gross morphology of the placenta, histology of cotyledons, and in-vitro culture of cotyledon cells to estimate endocrine function. Observations revealed that in comparison to gir cows, the Jaffrabadi buffalo have a heavier placenta with more cotyledons and trophoblast cell density. The cotyledon cells of buffaloes secrete higher levels of progesterone and estradiol-17β as compared to cattle. The age of the animal was found negatively correlated with placental weight and total cotyledons in both species.